2016
DOI: 10.23910/ijbsm/2016.7.6.1687
|View full text |Cite
|
Sign up to set email alerts
|

Extent of Knowledge and Level of Adoption of Hobbyists in Ornamental Fish Keeping and Aquarium Management in Tripura

Abstract: Aquarium fish keeping has been emerging as a popular hobby in Tripura. The study was conducted in the West Tripura district of Tripura in the year 2015-2016 among 100 randomly selected hobbyists of aquarium fish keeping. The data collected through observation and personal interview of the respondents revealed that majority of them were middle aged (36-50 years), all are literate and 50% of them were graduates. Around 39% of the hobbyists were businessmen. Further, the majority of the respondents (38%) were fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…In the present study, the ratio between male and female aquarium owners was male-skewed. The same phenomenon has also been reported in previous studies (Laskar et al, 2016). Felsing et al (2000) concluded that some cultural traditions and social limitations might result in females' lesser interest in keeping aquariums (Felsing et al, 2000).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In the present study, the ratio between male and female aquarium owners was male-skewed. The same phenomenon has also been reported in previous studies (Laskar et al, 2016). Felsing et al (2000) concluded that some cultural traditions and social limitations might result in females' lesser interest in keeping aquariums (Felsing et al, 2000).…”
Section: Discussionsupporting
confidence: 76%
“…In this survey, over 50% of the respondents from both the children/youth and adult groups agreed that aquariums have stress-relieving benefits. The results of a previous research indicated that only 10% of the respondents would choose aquariums to reduce tension in their daily lives under normal circumstances (Laskar et al, 2016). The spread of COVID-19 has had psychopathological effects on humans of all ages worldwide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ornamental fish market in the world for public aquaria is less than 1% at present, and over 99% of the market for ornamental fish is still confined to hobbyist (Selvarasu & Sankaran, 2011). The attraction, relatively minimum requirement of space and attention compared to other pet animals, is the reason for growing interest in keeping aquarium all over the world (Laskar et al., 2016). In the contemporary times of space restrictions and craze for beautifying interiors, the aquariums can become an integral element of homes, offices, hospitals, hotels, business establishments, airports and other institutions in Kenya.…”
Section: Resultsmentioning
confidence: 99%